Political management the dance of government and politics - Lees-Marshment, Jennifer (Routledge, 2021)
"Political Management lays out the core tools to manage government, campaigns and parties. The first book to combine management concepts with politics and government, it provides core theories for what Political Planning, Political HR, Political Organising, Political Leadership and Political Reviewing involve, illustrated with high level political practitioner interviews, examples and political documents. The text presents the 4 Ds of Political Management - Deliberating, Designing, Doing and Dancing - to convey that Political Management is more of a dance than a march. Even presidents and prime ministers do not have enough formal authority to control the myriad of practitioners, players, processes and policies involved in 21st century governance. In this book, the author demonstrates why political practitioners in campaign teams, parties, government departments and political offices need political management tools to utilise the resources they have available and overcome multiple obstacles that practical politics presents. By offering a clear sense of what political management involves and providing the theoretical frameworks to be used in empirical research, this book will stimulate significant future study. It will be invaluable to practitioners, scholars and students in politics, government, policy, leadership, management, public administration, and political management"--
2007
Keywords: Politik; Management; Politics, Practical; Political consultants; Political campaigns; Campaign management; Elections